Pregnancy-Associated Atypical Hemolytic Uremic Syndrome: A Case Report with MCP Gene Mutation and Successful Eculizumab Treatment - Domínguez-Vargas, Alex; Ariño, Fanny; Silva, Diana; González-Tórres, Henry J.; Aroca-Martinez, Gustavo; Egea, Eduardo; Musso, Carlos G. (American Journal of Perinatology Reports, 2024)
Pregnancy-associated atypical hemolytic uremic syndrome (P-aHUS) is a rare condition characterized by microangiopathic hemolytic anemia and kidney injury from thrombotic microangiopathy. P-aHUS occurs in approximately 1 in 25,000 pregnancies and is strongly related to complement dysregulation and pregnancy-related disorders, such as preeclampsia, eclampsia, and hemolysis, elevated liver enzymes, low platelet (HELLP) syndrome, resulting in adverse perinatal and fetal outcomes. Complement dysregulation in P-aHUS is commonly attributed to genetic mutations or autoantibodies affecting complement factors, including CFH, CFI, and MCP. We present a case of a 25-year-old primigravida who experienced severe preeclampsia and HELLP syndrome followed by the development of complicated P-aHUS during the early postpartum period. The patient exhibited severe clinical manifestations, including hypertensive emergency, central nervous system involvement, renal impairment, and microangiopathic hemolytic anemia. Timely initiation of eculizumab therapy resulted in successful disease remission. Further genetic analysis revealed a likely rare pathogenic MCP gene variant.
Keywords: aHUS; pregnancy; thrombotic microangiopathy; eculizumab; HELLP syndrome